Jatropha curcas, a biofuel crop: Functional genomics for understanding metabolic pathways and genetic improvement - Maghuly, Fatemeh (WILEY-VCH Verlag, 2013)
Jatropha curcas is currently attracting much attention as an oilseed crop for biofuel, as Jatropha can grow under climate and soil conditions that are unsuitable for food production. However, little is known about Jatropha, and there are a number of challenges to be overcome. In fact, Jatropha has not really been domesticated; most of the Jatropha accessions are toxic, which renders the seedcake unsuitable for use as animal feed. The seeds of Jatropha contain high levels of polyunsaturated fatty acids, which negatively impact the biofuel quality. Fruiting of Jatropha is fairly continuous, thus increasing costs of harvesting. Therefore, before starting any improvement program using conventional or molecular breeding techniques, understanding gene function and the genome scale of Jatropha are prerequisites. This review presents currently available and relevant information on the latest technologies (genomics, transcriptomics, proteomics and metabolomics) to decipher important metabolic pathways within Jatropha, such as oil and toxin synthesis. Further, it discusses future directions for biotechnological approaches in Jatropha breeding and improvement.